The New Penal Procedure Code (NCPP) of 2004, the communal jurisdiction and the peasant rounds - Bazán Cerdán, J. Fernando (2008)
This article examines the process of the progressive implementation of the new Criminal Procedural Code approved in 2004 in Peru, emphasizing the analysis of the content and scope of its article 18, which establishes the limits to the ordinary criminal jurisdiction for the knowledge of punishable acts, based on the constitutional recognition of the denominated indigenous special jurisdiction or communal jurisdiction established in article 149 of the Political Constitution of Peru of 1993, which ultimately raises various issues between the communal jurisdiction and the legal recognition of the attribution to solve conflicts by the peasant rounds, as well as the generation of potential factors of competence conflict between the ordinary criminal jurisdiction and the communal justice.